A standardized herbal combination of Astragalus membranaceus and Paeonia japonica promotes skeletal muscle hypertrophy in a treadmill exercise mouse model - Lee, Sung-Bae; Woo, Tae-Wook; Baek, Dong-Cheol; Son, Chang-Gue (Frontiers in Nutrition, 2024)
Background: Maintaining a normal range of muscle mass and function is crucial not only for sustaining a healthy life but also for preventing various disorders. Numerous nutritional or natural resources are being explored for their potential muscle hypertrophic properties. Aim: We aimed to evaluate the muscle hypertrophic effects of APX, a 1:1 mixture of Astragalus membranaceus and Paeonia japonica. In addition to the myotube differentiation cell assay, we utilized a weighted exercise-based animal model and evaluated changes in muscle hypertrophy using dual-energy X-ray absorptiometry (DXA) and histological analysis. Results: The 8-week treadmill exercise led to notable decreases in body weight and fat mass but an increase in muscle mass compared to the control group. Administration of APX significantly accelerated muscle mass gain (p < 0.05) without altering body weight or fat mass compared to the exercise-only group. This muscle hypertrophic effect of APX was consistent with the histologic size of muscle fibers in the gastrocnemius (p > 0.05) and rectus femoris (p < 0.05), as well as the regulation of myogenic transcription factors (MyoD and myogenin), respectively. Furthermore, APX demonstrated a similar action to insulin-like growth factor 1, influencing the proliferation of C2C12 myoblast cells (p < 0.01) and their differentiation into myotubes (p < 0.05) compared to the control group. Conclusion: The present study provides experimental evidence that APX has muscle hypertrophic effects, and its underlying mechanisms would involve the modulation of MyoD and myogenin.